Perceived employability skills of graduating students: implications for SMES - Juhdi, Nurita; Abu Samah, Ainon Jauhariah; Yunus, Shaharuddin (2006)
Companies and employers are complaining that they do not have enough supply of manpower despite the high rate of graduates produced by the higher learning institutions. It results in graduates being unemployed or getting jobs that do not commensurate with their qualification. Whilst the phenomenon of unemployed graduates has been attributed to a number of factors, one being the selective attitude of the graduates themselves, past studies have indicated that unemployment problem lies in the mismatch between the skills required by employers and those possessed by the potential employees. In general, the industry needs both the technical skills which most graduates have, and the soft skills, which unfortunately they lack. To ensure the employability of their graduates, higher education institutions, therefore, need to equip their students with the right skill set. This study aims to measure the employability skills among the final year undergraduate students in UNITAR. Eight variables that make up the employability skills namely communication skills, English language proficiency, ICT skill, team working skill, leadership skill, interpersonal skill, problem solving and adaptability skills. Data were collected through a set of questionnaire and a descriptive analysis of the data was done to find out the level of employability skills among the respondents. Students’ demographic data such as age, gender and area of specializations were used to compare their employability skills. Discussion and recommendations are then made based on the result of the analysis.